Translation urgency in our climate-challenged times: co-producing geographical knowledge on El Niño in Peru. - Laurie, N.; Healy, G.; Bell, I.; Calle, O.; Carmen, M.; Cornejo, S.; Davies, A.; Mendo, T.; Puescas, C.; Schofield, V.; Valdez, A.; White, R. M. (Scottish Geographical Journal)
This paper makes a case for revisiting the understandings of translation to enhance the co-production of geographical knowledge on climate change. Specifically, it offers insights about the potential role that schoolteachers and students can have as knowledge producers in relation to climate change by drawing on a case study of collaborative research on El Niño in Sechura, northern Peru. We call for researchers to pay greater attention to how co-production can be achieved through the integration of research agendas and practice with curricula development and innovation in school education. We contribute to work on how a generational shift in understanding about climate adaptation can be achieved through exploring communities' knowledge of the lesser-known opportunities of the El Niño phenomenon in northern desert regions. We conclude by arguing that revisiting how geography engages in and with translation is an urgent priority in climate-challenged times.